Principal Component Analysis of Growth, Leaf and Biomass Traits of Indian Willow (Salix tetrasperma Roxb.) - J. P. Sharma; H. P. Sankhyan; R.K. Gupta; S. K. Jha; Shikha Bhakta (International Journal of Economic Plants)
Indian willow (Salix tetrasperma Roxb.) genotypes were collected from 20 sites in North India covering Uttrakhand, Himachal Pradesh, Punjab and Jammu and Kashmir and one genotype from Rajasthan and evaluated in common garden test to study genetic variability in growth, leaf and biomass characters. Based on the principal component analysis, five components explained 82.85% of the total variance. The first component explained 44.29% of variance exhibited by biomass character. The second component accounted for 17.52% of total variation defined by leaf characters. Three characters, root shoot ratio, root length and the number of leaf teeth represented 9.31% of the variability in the third component. The fourth component accounted for 6.33% of variability that was represented by total foliage duration (0.730), and the fifth component accounted 5.39% of variability that was exhibited by leaf unfolding days (0.540). Scatter plot depicted a clear pattern of grouping of sites based on PC1 and PC2 variances.